Analysis of Linguistic and Non-Linguistic Features on Language Use in Whats App Chat Groups: English - Siti Hunadah; Shalihah, Imra'atus (Institut Agama Islam Tarbiyatut Tholabah, 2023)
This study aims to describe linguistic and non-linguistic features as well as the types of messages contained in the text of the susu_L wahtasapp chat group. the data used is the result of text conversations of members of the whatsapp group Susu_L. the technique used by the author is by taking pictures (captures or screen shots) from cellphones, then observing directly in the group to obtain data, and the last is conducting interviews with the group admins to obtain the information needed. The results of this study are the linguistic features contained in the text of the wahtasapp milk_L group in the form of morphemes, phrases and sentences and the nonlinguistic features contained in the chat group are in the form of emoticons. The types of messages used by group members are in the form of verbal messages and non-verbal messages.